Streptococcus pneumoniae Attenuated Strain SPY1 with an Artificial Mineral Shell Induces Humoral and Th17 Cellular Immunity and Protects Mice against Pneumococcal Infection - Zhang, Xinyuan; Cui, Jingjing; Wu, Yingying; Wang, Hong; Wang, Jian; Qiu, Yulan; Mo, Yunjun; He, Yujuan; Zhang, Xuemei; Yin, Yibing; Xu, Wenchun (Frontiers in Immunology, 2018)
Streptococcus pneumoniae is a major pathogen leading to substantial morbidity and mortality in children under 5 years of age. Vaccination is an effective strategy to prevent S. pneumoniae infection. SPY1 is a pneumococcal vaccine candicate strain obtained in our previous study. To improve its stability and immunogencity, in this study, we constructed the SPY1△lytA strain which lacks autolysin activity and was coated with an artificial exterior surface calcium phosphate shell by in situ mineralization. The resulting strain SPY1△lytACaPi displayed enhanced thermal stability enabling storage at 37oC for one week. Furthermore, mucosal and subcutaneous immunization with the SPY1△lytACaPi strain induced better protective effects than SPY1△lytA in anti-colonization after challenging with 19F and anti-invasion by D39 in mice. Subcutaneous immunization with SPY1△lytACaPi elicited higher IgG level while mucosal immunization primarily elicited an immune response which is supposed to be related to Th17 cells. Taken together, the mineralized strain may be a promising candidate for an attenuated S. pneumoniae vaccine.